Women's empowerment for sustainability in Africa - Dibie, Robert A., 1956- (Cambridge Scholars Publishing, 2018)
This book uses an open, explorative approach to deal with the different aspects of gender discrimination and gender empowerment policies, as well as their impact on economic development and capacity-building in several African countries. It uses primary and secondary data to present the argument that, without the full input of women, sustainable development will not be achieved in many African countries. This book is the first text written by knowledgeable gender issue experts that understand the culture of, and lived and conducted research in, Africa. It provides many examples of the relation.